1999
DOI: 10.1093/humrep/15.1.229
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes infiltrate the myometrium during human parturition: further evidence that labour is an inflammatory process

Abstract: Inflammatory mediators in the cervix, placenta and fetal membranes play a crucial role in human parturition. The aim of this study was to determine whether the upper and lower segments of the myometrium are infiltrated by inflammatory cells during pregnancy and parturition. Myometrial biopsies were obtained from non-pregnant women, and pregnant women at term before and after the onset of spontaneous labour. Subpopulations of inflammatory cells were identified using immunocytochemistry. The intercellular adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
207
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(219 citation statements)
references
References 34 publications
10
207
1
1
Order By: Relevance
“…Previous studies have characterized cytokine production by chorion and decidual cells and also identified the localization of cytokine receptors present (7,47,50,59). Apart from resident cells of these tissues, other potential sources of cytokine production are the lymphocytes that infiltrate as the onset of labor approaches (65)(66)(67). All the placentas used in this study were from patients undergoing elective Cesarean sections at term.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have characterized cytokine production by chorion and decidual cells and also identified the localization of cytokine receptors present (7,47,50,59). Apart from resident cells of these tissues, other potential sources of cytokine production are the lymphocytes that infiltrate as the onset of labor approaches (65)(66)(67). All the placentas used in this study were from patients undergoing elective Cesarean sections at term.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is an important component of the parturition process in eutherian mammals, and infection can cause preterm labor (68,69). In wallabies, inflammatory prostaglandins are sufficient to induce parturition behavior, and blocking prostaglandin activity late in gestation results in the extension of pregnancy (70,71).…”
Section: Evolution and Function Of The Attachment Reaction During Thementioning
confidence: 99%
“…Given that eutherian parturition, like implantation, is an inflammatory process (11,68), and the attachment reaction in the opossum is inflammatory, an interesting hypothesis is that both implantation and parturition are proinflammatory reactions because they are both derived forms of the therian attachment reaction (Fig. 8).…”
Section: Evolution and Function Of The Attachment Reaction During Thementioning
confidence: 99%
“…At its most basic level, this concept is supported by the demonstration that leukocytes, (largely neutrophils and macrophages, and also T cells) invade the myometrium, cervix and fetal membranes at or immediately after the onset of labour (Osman et al, 2003, Thomson et al, 1999, attracted by increased tissue expression of chemokines and cell adhesion molecules (Ledingham et al, 2001, Winkler et al, 1998. In parallel, leukocytes circulating in the peripheral blood increase their expression of cell adhesion molecule ligands such as CD11a and CD11b (Yuan et al, 2009), facilitating leukocyte emigration into the myometrium and cervix.…”
Section: Labour As An Inflammatory Eventmentioning
confidence: 99%